The ‘dilemma of authority’ in the 21st Century: A critical discourse analysis of a student attendance and engagement data monitoring policy at a UK university - Roberts, Ruth M. (Critical Education)

(untitled) (Institute for Critical Education Studies / UBC, 2023)
This paper offers a critical discourse analysis of documents relating to the introduction of predictive learning analytics at a small, UK university. Semiotic and interdiscursive analysis was carried out on texts from three different sources: the institution, the commercial analytics software provider, and one academic subject area. Authority discourses in institutional texts indicate an ambivalent attitude to students exemplified by oscillating discourses of ‘Here to help’ and ‘Over to You’. At the micro level, the ‘Concerned Tutor’ discourse indicates a diminished authority position for academics, who are nevertheless charged with managing student engagement on the ground. The paper posits a shift in discursive positioning of the student from ‘consumer’to ‘asset’ and suggests that learning analytics policies are performative in nature. They provide auditable evidence of institutional efforts to improve student engagement, while failing to address contextual factors that lead to non-engagement and attrition.